Pengembangan Media Mini Book untuk Meningkatkan Kemampuan Membaca pada Mata Pelajaran Bahasa Indonesia di Kelas V - Pitri Situmorang; Rina Devianty; Muhammad Syaifullah (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research is entitled "Development of Mini Book Media to Improve Reading Ability in Indonesian Language Subjects in Class V" which is based on initial observations that there are class V students at SDS Prguruan Kebangsaan Medan who experience difficulties in reading. This research aims to develop and evaluate learning media in the form of mini books to improve the reading skills of class V students. The method used is research and development with 4D model design through the stages of definition, design, development and distribution. The results of the research show that the mini book media is very valid, practical and effective in improving reading skills with good quality and is suitable for learning in class V. It is recommended that this mini book media can be used by teachers to improve reading skills in Indonesian language subjects in class V.